Criminal Liability in Prison Fire Case: A Case Study of Class I Tangerang Prison Fire - Supriyono, Supriyono; Ihsan, Ahmad Yulianto (IJCLS (Indonesian Journal of Criminal Law Studies), 2022)
The existence of Correctional Institutions is part of the criminal system in Indonesia. The criminal law policy which is not yet ideal and the management of prisons that are not optimal have caused over capacity in all prisons. Therefore, in the event of a prison fire disaster, mitigation and rapid evacuation of the inmates cannot be carried out and cause death toll. When there are inmates who die as a result of a prison fire, of course, there must be a party who is responsible politically, sociologically and juridically. This study aims to determine criminal liability in prison fire cases based on the Criminal Code, Law Number 12 of 1995 concerning Corrections and other laws and regulations. This research uses normative juridical research method. Based on the results of the study, it can be seen that politically and sociologically those responsible for the fire incident were government officials who handled prison affairs, namely the Minister of Law and Human Rights, the Director General of Corrections, and the head of the prison. While juridically those responsible for the prison fire incident were the perpetrators who were found guilty either by intention or negligence, namely the prison officer for general affairs who handled prison electricity and the prison warden on duty when the fire occurred. To prevent prison fires from causing the inmates to die, it is expected that the government, will improve prison management and carry out criminal law policy reform to improve the criminal system in Indonesia.